A comparative study of bulk leach extractable gold (BLEG) and fire assay methods on the Wassa deposit at Golden Star Limited, Wassa mine - Tawiah, Christain; Manu, Johnson; Nunoo, Samuel; Hayford, Ebenezer (International Journal of Basic and Applied Sciences, 2018)
Golden Star Resources Limited conducts Bulk Leach Extractable Gold (BLEG) and Fire Assay methods on samples from its exploration program. Additionally, for mining control and as part of the sampling and analytical protocol, residues of samples whose assay values are greater than 10 g/t are subjected to fire assay to determine the quantity of gold. However, there is gold retained in the tails or residue after leaching and to verify the suitability and efficiency of the analytical method, drill samples (RC and DD) with control samples were analysed using BLEG method based on the accelerated cyanide leach extraction and Fire Assay method on the tails.Percentages of the prepared samples were subjected to BLEG orientation study to investigate the leachability and efficiency of the BLEG method on the ore samples. Fire Assay analysis was also carried out on the selected tailing samples to find out the assay reproducibility of the samples. The analytical analyses carried out on the samples revealed that the ore samples were leachable with gold recovery levels ranging between 96% and 100% when there is total pulverization of samples to make BLEG method possible and that this procedure is also cheaper than the conventional Fire Assay.
Keywords: Birimian; BLEG; Fire Assay; Gold Recovery; Tailings.